The Guidelines on the Improvement in the Staff – Lecturers’ Quality of Life in Souphanouvong University - INDAVONG, Dalounny; HOONGSENGPHA, Soudtida; KHOMTHAVONG, Phonepasith; Phumma, Somphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The Purpose of this Research were: 1) to study Staff – Lecturers’ quality of life in Souphanouvong University, 2) to study factor influencing the staff – Lecturers’ quality of life in Souphanouvong University and 3) to analyes the Guidelines on the Improvement in staff –lecturers’ quality of Life in Souphanouvong University. The samples were 208 lectures who have taught and worked there in 2019. The instruments inclcuded, questionaires, which were used by 5-Point Likert Scale. The cronbach alpha reliability coefficient was 0.977. Statistical methods used in data analysis were descriptive statistics, which summarize data from a sample using indexes such as the mean or standard deviation, Pearson Product-Moment Correlation Coefficients and Multiple Regression and Correlation Coefficient. The major findings found that: overall, the Lecturers’ quality of life was at a fairly good level, factors influencing staff and lectuerers’s quality of life at Souphanouvong University consisted of, social Influence factor, Economic Development need factor, Family development need factor ​and Social Development need factor. Staff – Lecturers’ Quality of Life in Souphanouvong University was found statistically significant at 0.01. There were two possible approaches to the guidelines on Improvement on the Staff –Lecturers’ Quality of Life in Souphanouvong University. The first approach was for Souphanouvong University (Insitution) and another was for Staff – Lecturers.